“THE EFFECT OF CELEBRITY ENDORSMENT TOWARDS PURCHASING INTENTION THROUGH BRAND PERCEPTION AS INTERVENING VARIABLE ON SHOPEE CONSUMERS DURING THE COVID-19 PANDEMIC” - Agus Prasetyo; Andhy Tri Adriyanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The development of technology, especially the internet, has changed the lifestyle and human behavior, one of which is shopping style. This study aims to determine the effect of Celebrity Endorsement towards Purchasing Intention with Brand Perception as an intervening variable on Shopee e-commerce customers in Semarang City. The population in this study was Shopee e-commerce users in Semarang city and the number of samples was 96 respondents, which obtained by using purposive sampling. This study used quantitative method and source of data was obtained from primary data and secondary data. Data was analyzed using Structural Equation Modeling (SEM) with Smart PLS version 3.2 software. The results of this study indicate that Celebrity Endorsement had a significant effect on Brand Perception and Purchasing Intention, and Brand Perception had a significant effect on Purchasing Intention. The Brand Perception variables was able to mediate the relationship between the influence of Celebrity Endorsement on Purchasing Intention